Propofol-based Total Intravenous Anesthesia Is Associated with Better Survival Than Desflurane Anesthesia in Colon Cancer Surgery. (November 2018) - Wu, Zhi-Fu; Lee, Meei-Shyuan; Wong, Chih-Shung; Lu, Chueng-He; Huang, Yuan-Shiou; Lin, Kuen-Tze; Lou, Yu-Sheng; Lin, Chin; Chang, Yue-Cune; Lai, Hou-Chuan
Editor's Perspective: What We Already Know about This Topic: Propofol may better preserve host defenses against cancer Whether cancer recurrence is less likely with propofol than volatile anesthesia remains unknown What This Article Tells Us That Is New: The authors conducted a propensity-matched retrospective analysis of 1, 158 patients who had colon cancer surgery Patients anesthetized with propofol had better overall survival Background: Previous research has shown different effects of anesthetics on cancer cell growth. Here, the authors investigated the association between type of anesthetic and patient survival after elective colon cancer surgery. Methods: A retrospective cohort study included patients who received elective colon cancer surgery between January 2005 and December 2014. Patients were grouped according to anesthesia received: propofol or desflurane. After exclusion of those who received combined propofol anesthesia with inhalation anesthesia or epidural anesthesia, survival curves were constructed from the date of surgery to death. After propensity matching, univariable and multivariable Cox regression models were used to compare hazard ratios for death. Subgroup analyses were performed for tumor–node–metastasis staging and postoperative metastasis. Results: A total of 706 patients (307 deaths, 43.5%) with desflurane anesthesia and 657 (88 deaths, 13.4%) with propofol anesthesia were eligible for analysis. After propensity matching, 579 patients remained in each group (189 deaths, 32.6%, in the desflurane group vs. 87, 15.0%, in the propofol group). In the matched analyses, the propofol-treated group had a better survival, irrespective of lower tumor–node–metastasis stage (hazard ratio, 0.22; 95% CI, 0.11 to 0.42; P < 0.001) or higher tumor–node–metastasis stage (hazard ratio, 0.42; 95% CI, 0.32 to 0.55; P < 0.001) and presence of metastases (hazard ratio, 0.67; 95% CI, 0.51 to 0.86; P = 0.002) or absence of metastases (hazard ratio, 0.08; 95% CI, 0.01 to 0.62; P = 0.016). Simple propensity score adjustment produced similar findings. Conclusions: Propofol anesthesia for colon cancer surgery is associated with better survival irrespective of tumor–node–metastasis stage. Abstract : The authors conducted a propensity-matched retrospective analysis of 1, 158 patients who had colon cancer surgery. Patients anesthetized with propofol had better overall survival.